Adolescents’ judgments of a refusal statement in Malayalam: A metapragmatic approach to conversation analysis of children with Specific Learning Disability - Geethi S. Shyamala K. Chengappaa (Journal of All India Institute of Speech and Hearing, 1970)
A group of children with Speci c Learning Disability (SLD) ranging from 12;0 - 14;11 years were compared against a group of age matched typicallydeveloping children while investigating their metapragmatic skills. Children's verbal judgements of an expression of refusal statement in a conversationalact were used for this purpose. Findings revealed a developmental progression in children's metapragmatic awareness during the adolescent ages. Theresults also indicated that children with SLD performed less well than typical children. This dierence may be probably attributed to these children'spoor language processing skills especially with regard to their choice of words, speech acts and impairments in social perception.